Effect of Colloidal Silicate on the Migration Behaviour of Strontium in Groundwater Environment of Geological Disposal Candidate Site. (23rd September 2019) - Zuo, Rui; Han, Kexue; Shi, Rongtao; Ding, Fei; Liu, Li; Wang, Jinsheng; Teng, Yanguo; Yang, Jie; Liu, Xin
Abstract : Various colloids are present in the natural groundwater environment, and colloids act on the processes involved when radionuclides leak from a repository in a high-level waste disposal site. This paper investigates the effect of colloidal silicate in natural groundwater environments on the migration behaviour of Sr(II). Three different experimental cases have been designed: (1) effect in the presence of colloidal silicate, (2) effect in the presence of a porous medium, and (3) effect in the presence of both colloidal silicate and porous medium (referred to as CS, PM, and PC, respectively). Batch experiments were used to study the effect of influencing factors on Sr(II) migration behaviour, such as the amount of CS, solid-to-liquid ratio, pH, contact time, and initial concentration of Sr(II). The experiments showed that the effect of PC on the migration behaviour of Sr(II) was greatest, and the presence of CS enhanced the sorption. The colloid amount, pH, and solid-to-liquid ratio significantly affected the migration behaviour. The more the colloids were added, the better the adsorption effect. The optimal pH and solid-to-liquid ratio were 6 and 20 : 1, respectively. The alkaline environment is more conductive to colloid sorption. When the solid-to-liquid ratio was 20 : 1, the sorption percentage of PC is 0.5 times larger than PM. Although the PC has a longer adsorption equilibrium time, the percentage of adsorption can be larger than that in the other two cases. The kinetics and isotherms of Sr(II) were best described by the pseudo-second-order and Langmuir models. It was inferred that strong chemical interactions and/or surface complexation contributed primarily to Sr(II) sorption, and the process was on the monolayer adsorption of the outer surface. These findings provide valuable information for the migration behaviour of strontium in groundwater environments of geological disposal site. At the same time, it provides information for the implementation of permeable reactive barrier technology to control the transport of radioactive Sr(II) and its species in natural surface and groundwater.